Comparing the effect of Hypoalbuminemia on Sodium measured by Indirect versus Direct Ion Selective Electrode Method - Paracha, Athar Iqbal; Haroon, Zujaja Hina; Aamir, Muhammad; Bashir, Saima; Bibi, Afshan; Javaid, Haroon (Pakistan Armed Forces Medical Journal, 2023)
Objective: To evaluate the effect of low serum Albumin levels on serum sodium measurement when analyzed by the indirect Ion Selective Electrode (ISE) method and to compare the results with the direct Ion selective electrode (ISE) method. Study Design: Cross-sectional study Place and Duration of Study: Department of Chemical Pathology, Armed Forces Institute of Pathology, Rawalpindi Pakistan, from Jan to Mar 2021. Methodology: Patients of either gender, aged 18 to 70 years, who were admitted to the Intensive Care Unit of Combined Military Hospital, Rawalpindi, were selected. A total of 200 blood samples were collected in a gel tube. Serum samples were analyzed for albumin and sodium within two hours of sample collection. Sodium levels were measured concurrently by both direct and indirect ISE methods. The difference in results between these two techniques was studied. Results: Hypoalbuminemia was detected in 176(88%) patients, while 24(12%) had normal albumin levels. In Hypoalbuminemic patients, serum sodium measurements were higher using the indirect ISE method(134.07±5.55) compared to the direct ISE method (130.95±6.04); the difference between the two techniques was statistically significant (p-value <0.001).Pearson correlation coefficient (r-value = -0.86, p-value <0.001) revealed a symmetrical increase in differences between the two methods as the albumin level decreased. Conclusion: In Hypoalbuminemic patients, the indirect ISE method gave falsely raised results of serum sodium. In such patients, serum sodium measurement by the Direct ISE method offers more accurate and consistent electrolyte results.